Strategi Pengembangan Obyek Wisata Religi Bukit Surowiti di Kecamatan Panceng, Gresik - Tisa Angelia; Eddy Imam Santoso (Universitas Muhammadiyah Mataram, 2019)
Gresik Regency is an industrial area which is also one of the famous tourist destinations in East Java with a variety of tourism potentials, namely natural tourism, cultural tourism and religious tourism. Religious tourism is spread across several regions in Gresik and is developed to increase regional income. These religious tourism objects include guardian tourism and some Islamic religious tourism. Tourism Sunan Giri and Maulana Malik Ibrahim are two religious tourism objects that are visited by many tourists and become an icon of Gresik City as the Tourism City of Wali. Surowiti Hill Tourism is one of the attractions in Gresik which consists of religious tourism objects consisting of Islamic tombs and religious leaders, and cave-shaped nature tourism. However, in its development, Bukit Surowiti Tourism, which is in contact with Bukit Jamur Tourism and Dalegan Beach Tourism, has not been optimally managed and promoted. This study aims to determine the potential of Surowiti Hill Tourism and then formulate a strategy for developing religious tourism.This research uses exploratory research methods with SWOT analysis techniques. Explorative research is carried out by searching and gathering information to formulate a hypothesis. Research factors and factors that are related to other factors are natural potential and ancestral heritage are Islamic leaders and tombs, as well as the emergence of well-known religious tourism such as Wali Sunan Giri and Maulana Malik Ibrahim Tourism, nature tourism such as Bukit Jamur Tourism and Dalegan Beach Tourism in Gresik , factors of weakness from weather demands, water supply and inadequate accessibility, and safety factors, the lack of community and government support, as well as the increasing industrial development in Gresik. Furthermore, the factors that are expected to be a reference and contribution to local governments in formulating strategies for developing religious tourism in Surowiti Hill.